Pengaruh Profitabilitas dan Financial Distress Terhadap Tax Avoidance dengan Corporate Governance Sebagai Variabel Pemoderasi - Fadillah Egiana; Dade Nurdiniah (UNIVERSITAS KALBIS, 2022)
This research aims to test empirically the effect of profitability and financial distress towards tax avoidance with corporate governance as measured by independent board of commissioners, institutional ownership, and managerial ownership as moderating variable. This research used quantitative data from trading and servicecompanies listed in Indonesia Stock Exchange (BEI) during the year 2016-2018, with theselection of sample used purposive sampling method, and the testing of hypothesis used multiple regression analysis. The result of this research showed that profitability has influenceon tax avoidance and financial distress has influence on tax avoidance. The independent board of commissioners and managerial ownership do not moderate the influence of the profitability and financial distress on tax avoidance, butmoderate of the institutional ownership has influenceof the profitability and financial distress on taxavoidance.